Bimbingan Agama Islam Dalam Meningkatkan Ketenangan Jiwa Warga Binaan Di Lembaga Pemasyarakatan - Zulkifli Zulkifli (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
Humans are the most perfect creatures that God created compared to others, because humans have thoughts and feelings that other creatures do not have. God revealed Islam as a guide for humans so they would not be easily lost. Religion is a benchmark for someone to do an act, because in religion there are rules that God gives in living life. The rules are not limited to human relations with God, but the rules of relations between humans and relations with their environment. Symptoms of insecurity in one's soul are easily anxious, fearful, emotional overflowing and uncontrollable, so that he cannot be friends with himself or with other people. Someone needs a mentor in the process of self-recognition and religion. It takes a variety of processes to get to know the religion of Islam, namely with the help of a counselor who provides an understanding that can be accepted by the person so that it becomes a reference in life, then someone who has a calm soul is protected from symptoms of mental disorders. Good religious formation, theoretically will produce good results for humans. Likewise religious guidance for good female prisoners will also give birth to the character of prisoners for themselves and the community. However, the phenomena found are still some of those who were netted in the same case several times, which are clearly prohibited by religious and community norms